(untitled) (Al-Academy, 2026)
Since its inception, cinema and television have witnessed a multiplicity of uses and exploitation through a large set of phenomena that included film production, which cast its shadow on the filmmaking industry by relying on the workings of the elements of cinematic language and the inclusion of forms with content to convey intended concepts, until it was considered an artistic phenomenon that occupied a large space and in multiple directions and with differences in the nature of the artistic and dramatic treatment, in a clear reliance by content creators on cinema and television as a means of expression that carries essential and aesthetic connotations. Based on the above, the researcher summarized the research problem by raising the following question: What are the methods and intellectual and ideological foundations in which the artistic treatment is carried out to build the visual employment of Zionist ideological thought in world cinema?